Waterlogging Tolerance and Recovery in Canopy Development Stage of Cassava (Manihot esculenta Crantz) - Sukanda Kerddee; Pasajee Kongsil; Sutkhet Nakasathien (AGRIVITA, Journal of Agricultural Science, 2021)
Cassava is susceptible to waterlogged soil. In order to find the right variety for breeding purposes, a research needs to find proper screening parameters. They must be easy, fast, and economical practice. Therefore, in this research, upper-ground morphological responses of cassava to water deficit conditions in tissue were evaluated as traits to screen cassava breeding lines for water-logging tolerance. Hanatee variety is a landrace grown in the well-watered field for cooking purpose and was bred with Kasetsart 50 which is a high yielding commercial variety. These two varieties together with five breeding lines have water-logging tolerance potential in the field. They were evaluated in the pot for waterlogging stress at two vegetative growth stages at 105 DAP and 165 DAP for 12 days in each stress period. Among these seven varieties/lines, there were no varieties/lines showing waterlogging tolerance under this condition over others, but all showing recovery response. The results indicated that cassava at the vegetative growth stage had a recovery mechanism for the upper-ground parts, but not for the storage root tissue after waterlogging stress for 12 days. There was a potential of using the ratio of leaf retention to screen cassava germplasm or breeding lines for waterlogging tolerance.